2017
DOI: 10.18533/ijbsr.v7i4.1031
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Fiji’s Export and Its Impact on Economic Growth

Abstract: Exports are vital for Fiji's economy as it contributes significantly to its gross domestic product (GDP) and economic growth. The export data over the years show very slow growth and is gradually increasing. Fiji's GDP data show that GDP is gradually increasing. Thus, Fiji's economic growth is also increasing at a steady rate. This study aims to measure the relationship between exports and economic growth in Fiji. A regression analysis on data collected for Fiji from 2000-2015 shows that there is a strong posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 10 publications
1
6
1
Order By: Relevance
“…This might find its justification in the fact that most of high income developing countries enjoy high consumption level which resulted in importing final goods rather than a factor of production. This result is similar to that obtained by Altaee et al (2016), Taghavi (2012), Greenway and Hine (2003), and Raj & Chand (2017).…”
Section: Data Analysis and Resultssupporting
confidence: 92%
“…This might find its justification in the fact that most of high income developing countries enjoy high consumption level which resulted in importing final goods rather than a factor of production. This result is similar to that obtained by Altaee et al (2016), Taghavi (2012), Greenway and Hine (2003), and Raj & Chand (2017).…”
Section: Data Analysis and Resultssupporting
confidence: 92%
“…In other words, when net exports experienced shocks (increase), then it is assumed they will reduce economic growth. These results are not consistent with the hypothesis formulated and did not support findings by Raj and Chand, (2017); Tsen (2007) who revealed that net exports have a significant positive effect on economic growth.…”
Section: Discussioncontrasting
confidence: 87%
“…The results showed that there is a one-way relationship where economic growth encourages net exports in Indonesia, Malaysia, the Philippines, and Thailand. Raj and Chand (2017) found that there is a strong positive relationship between exports and economic growth. Furthermore, a prior study by Hye et al (2016) found that export value was the key to the success of China's economy both in the short and long term in the 1975-2009 period.…”
Section: H2mentioning
confidence: 99%
“…1a). The downward trend has been attributed to structural problems facing Fiji's commodity exports (especially the sugar industry), the lack of investment, adverse weather conditions, and declining productivity (Narayan and Prasad 2003;Narayan and Narayan 2004;Raj and Chand 2017). It could also be due to a reduced drive to promote these industries further by adopting creative ideas in secondary production, getting private investors to advance creative destruction, and exploring new areas of exports.…”
Section: Trends In Fiji Exportsmentioning
confidence: 99%